2020
DOI: 10.1101/2020.12.09.20246413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical characteristics of critically ill patients with COVID-19

Abstract: ObjectiveDescribe the clinical and respiratory characteristics of critical patients with coronavirus disease 2019 (COVID-19).DesignObservational and retrospective study over 6 months.SettingIntensive care unit (ICU) of a high complexity hospital in Buenos Aires, Argentina.PatientsPatients older than 18 years with laboratory-confirmed COVID-19 by reverse transcriptase-polymerase chain reaction (RT-PCR) for SARS-CoV-2 were included in the study.Variables of interestDemographic characteristics such as sex and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(123 reference statements)
1
2
0
2
Order By: Relevance
“…The average age was 42 years for women and 45 years for men. The average age was similar to the averages observed in India 20 and Peru 21 and lower than the averages observed in China 22 , Europe 23 , Argentina 24 and Australia 25 . The age averages are compatible with the age of the economically active population of the assessed municipalities.…”
Section: Discussionsupporting
confidence: 73%
“…The average age was 42 years for women and 45 years for men. The average age was similar to the averages observed in India 20 and Peru 21 and lower than the averages observed in China 22 , Europe 23 , Argentina 24 and Australia 25 . The age averages are compatible with the age of the economically active population of the assessed municipalities.…”
Section: Discussionsupporting
confidence: 73%
“…A total of 90 studies (82 retrospectives, 5 prospective, 3 cross-sectional) out of 7352 identified publications were included after satisfying the inclusion criteria (Figure 1). While 44 articles 41,42,44,46,47,49,[73][74][75][76][78][79][80]101,[103][104][105][106][108][109][110][111] assessed baseline NLR as a predictor for determining only severity, 32 articles 24,25,[29][30][31][32][33][34][38][39][40]43,45,48,77,[82][83][84][85][86][87][88][89][90][91][92]…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…Aunque los pacientes con neumonía por SARS-CoV-2 asociada a SDRA presentan la mediana de la Cst mayor de 41 [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] mL/cmH 2 O que en los pacientes con SDRA clásico con 32 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] mL/cmH 2 O. La extensión del edema pulmonar en los pacientes con COVID-19 medidos por el peso pulmonar total con tomografía computarizada de tórax fue similar a los pacientes con SDRA clásico.…”
Section: Discussionunclassified
“…Otros grupos sudamericanos han reportado valores similares. 31 Los pacientes ventilados en PP constituyen cerca de la mitad de la población estudiada y se caracterizan por presentar puntajes de gravedad similares a los pacientes ventilados en PS; sin embargo, la mortalidad es elevada (32.1%). Esto se correlaciona con altas Pva, PaO 2 /FiO 2 más bajas en SU e IMC y peso mayor que los pacientes ventilados en supino (Tabla 2).…”
Section: Discussionunclassified